Integrated Site Investigation Procedure (ISIP) for Managing Infrastructure Development - Omar R.C.; Taha H.; Baharuddin I.N.Z.; Solemon B.; Roslan R.; Wahab W.A.; Fared M.M.; Hashim W.N.S.W. (Springer Science and Business Media Deutschland GmbH, 2023)
Cost effectiveness; Decision making; Hazards; Information management; Landslides; Risk assessment; Risk management; Zoning; And system; Infrastructure development; Integrated sites; Landslide hazard; Landslide risk managements; Malaysia; Methodology; New approaches; Risk evaluation; Site investigations; Risk analysis